An Analysis of Politeness Strategies Used in Webtoon Conversation Entitled Nano List - Siti Nadila Marsya; I Wayan Juniartha; Ni Nyoman Deni Ariyaningsih (International Journal of English Learning and Applied Linguistics (IJELAL), 2021)
The study concerns with the politeness strategies that occur in the conversation uttered by the characters in Webtoon entitled Nano List. This study aims at analyzing the reasons of applying politeness strategies between the characters in Webtoon entitled Nano List. This study used descriptive qualitative method to analyze and arrange the data which means that the collected data were analyzed by the reason of using certain politeness strategies. The data related with the reason of applying politeness strategies were analyzed using Social Factors theory by Holmes and supported by Face-Threatening Act theory by Brown and Levinson. The result of the study shows that there are four aspects of Social Factors which influence the use of politeness strategies, those are Participant, Setting, Topic and Function of the Interaction. Participant of the Interaction was most frequently used in the conversation between the characters in the Webtoon entitled Nano List because the characters in that Webtoon mostly want to show their friendliness towards the hearer.